Cardiac SNARE Expression in Health and Disease - Bowman, Peter R. T.; Smith, Godfrey L.; Gould, Gwyn W. (Frontiers in Endocrinology, 2019)
SNARE proteins are integral to intracellular vesicular trafficking, which in turn is the process underlying the regulated expression of substrate transporters such as the glucose transporter GLUT4 at the cell surface of insulin target tissues. Impaired insulin stimulated GLUT4 trafficking is associated with reduced cardiac function in many disease states, most notably diabetes. Despite this, our understanding of the expression and regulation of SNARE proteins in cardiac tissue and how these may change in diabetes is limited. Here we characterise the array of SNARE proteins expressed in cardiac tissue, and quantify the levels of expression of VAMP2, SNAP23 and Syntaxin4 - key proteins involved in insulin-stimulated GLUT4 translocation. We examined SNARE protein levels in cardiac tissue from two rodent models of insulin resistance, db/db mice and high-fat fed mice, and show alterations in patterns of expression are evident. Such changes may have implications for cardiac function.